The Use of Tarpaulins on the Body of a Pickup Truck on Airflow Patterns and Pressure Distribution Characteristics: An Experimental Study - I Kadek Arya Bayu Diloka; Anak Agung Adhi Suryawan; Ainul Ghurri (HM Publisher, 2022)
The installation of tarpaulins on the body of pickup trucks is often used to protect goods from heat and rain, which affect airflow patterns, pressure distribution, and vehicle aerodynamics. This research was conducted to determine the airflow pattern and pressure distribution characteristics such as static pressure, dynamic pressure, and pressure coefficient that affect the performance of a tarpaulin-fitted pickup truck. Experimental tests were carried out on 6 specimens, namely pickup trucks without using a tarp or baseline, pickup trucks fitted with tonneau cover tarpaulins (type A), Aerocap tarpaulins with an angle of 0° (type B) and 12° (type C), and Cincing tarpaulins with foot angle of 30° (Type D) and 15° (Type E) in the wind tunnel at a speed of 5.47 m/s. The results showed that the more aerodynamic the use of tarpaulins resulted in a streamlined flow pattern, as shown by the use of 12° aerocap tarpaulins, which had more aerodynamic flow and the most stable fluctuations in the Cp value, blockage mass, and smaller obstacles compared to other pickup trucks.